Sirtuin 5 as a novel target to blunt blood–brain barrier damage induced by cerebral ischemia/reperfusion injury. (1st June 2018) - Diaz-Cañestro, Candela; Merlini, Mario; Bonetti, Nicole R.; Liberale, Luca; Wüst, Patricia; Briand-Schumacher, Sylvie; Klohs, Jan; Costantino, Sara; Miranda, Melroy; Schoedon-Geiser, Gabriele; Kullak-Ublick, Gerd A.; Akhmedov, Alexander; et al.
Abstract: Background: In acute ischemic stroke (AIS) patients, impaired blood–brain barrier (BBB) integrity is associated with hemorrhagic transformation and worsened outcome. Yet, the mechanisms underlying these relationships are poorly understood and consequently therapeutic strategies are lacking. This study sought to determine whether SIRT5 contributes to BBB damage following I/R brain injury. Methods and results: SIRT5 knockout ( SIRT5 −/− ) and wild type (WT) mice underwent transient middle cerebral artery (MCA) occlusion (tMCAO) followed by 48 h of reperfusion. Genetic deletion of SIRT5 decreased infarct size, improved neurological function and blunted systemic inflammation following stroke. Similar effects were also achieved by in vivo SIRT5 silencing. Immunohistochemical analysis revealed decreased BBB leakage and degradation of the tight junction protein occludin in SIRT5 −/− mice exposed to tMCAO as compared to WT. In primary human brain microvascular endothelial cells (HBMVECs) exposed to hypoxia/reoxygenation (H/R), SIRT5 silencing decreased endothelial permeability and upregulated occludin and claudin-5; this effect was prevented by the PI3K inhibitor wortmannin. Lastly, SIRT5 gene expression was increased in peripheral blood monocytes (PBMCs) of AIS patients at 6 h after onset of stroke compared to sex- and age-matched healthy controls. Conclusion: SIRT5 is upregulated in PBMCs of AIS patients and in the MCA of WT mice exposed to tMCAO; SIRT5 mediates I/R-induced brain damage by increasing BBB permeability through degradation of occludin. This effect was reproduced in HBMVECs exposed to H/R, mediated by the PI3K/Akt pathway. Our findings shed new light on the mechanisms of I/R-dependent brain damage and suggest SIRT5 as a novel therapeutic target. Highlights: SIRT5 −/− mice display decreased stroke size and neurological deficits after stroke. SIRT5 −/− mice present reduced BBB leakage and occludin degradation. SIRT5 silencing increases endothelial resistance and TJPs in HBMVECs. SIRT5 gene expression increases in PBMCs of AIS patients.